Mourning One’s Own Mortality: Analysis of Kazuo Ishiguro’s Never Let Me Go - Rendila Restu Utami (Balai Bahasa Provinsi Bali, 2023)
Mortality is one of the aspects of the cycle of life that are feared by humans since it is inevitable. This article investigates Kazuo Ishiguro's work entitled Never Let Me Go, a dystopian novel set in England in a fictional world in the 90s, further. The novel tells the story of a woman named Kathy H. and is told from her perspective and highlights her life’s story growing up at a private school called Hailsham. The novel is analyzed using close reading through the lens of mourning and melancholia as well as the concept of memory. Kathy H.'s narrative of remembering and retelling past events is something that is emphasized in this study. It can be gathered that Kathy H.'s narration of remembering and retelling events in her past as an unreliable narrator and as a clone reveals herself as an individual and that telling her story is her way of coping with all the losses she experienced throughout her life and her way of accepting and mourning her own impending death.AbstrakMortalitas merupakan salah satu aspek siklus kehidupan yang ditakuti manusia karena hal ini tidak dapat dihindari. Artikel ini menyelidiki lebih jauh karya Kazuo Ishiguro yang berjudul Never Let Me Go, sebuah novel distopia dengan latar Inggris yang ada dalam dunia fiksi pada tahun 90-an. Novel bercerita tentang seorang wanita bernama Kathy H. dan dikisahkan dari sudut pandangnya dan mengangkat seluk beluk kehidupannya saat tumbuh besar di sebuah sekolah swasta bernama Hailsham. Novel dianalisis menggunakan close reading melalui lensa mourning (berkabung) dan melancholia (melankolia) serta konsep ingatan. Narasi Kathy H. mengingat dan menceritakan kembali peristiwa masa lalu menjadi hal yang digarisbawahi dalam studi ini. Dapat disimpulkan bahwa penarasian Kathy H. mengingat dan menceritakan kembali kejadian pada masa lalunya sebagai seorang unreliable narrator dan seorang klon menunjukkan dirinya sebagai seorang individu serta mengungkap hal tersebut adalah caranya menghadapi semua kehilangan yang dialami sepanjang hidupnya dan juga caranya untuk menerima dan berkabung atas kematiannya sendiri yang akan datang.